5x+5=3(3x-4)-10x

Simple and best practice solution for 5x+5=3(3x-4)-10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+5=3(3x-4)-10x equation:



5x+5=3(3x-4)-10x
We move all terms to the left:
5x+5-(3(3x-4)-10x)=0
We calculate terms in parentheses: -(3(3x-4)-10x), so:
3(3x-4)-10x
We add all the numbers together, and all the variables
-10x+3(3x-4)
We multiply parentheses
-10x+9x-12
We add all the numbers together, and all the variables
-1x-12
Back to the equation:
-(-1x-12)
We get rid of parentheses
5x+1x+12+5=0
We add all the numbers together, and all the variables
6x+17=0
We move all terms containing x to the left, all other terms to the right
6x=-17
x=-17/6
x=-2+5/6

See similar equations:

| (6x+7)=(3x+16) | | (6x+7)=(3x=16) | | 2+3x=-4(5+x2) | | -5n+5n(n-7)=-40+5n | | 108=(21x+3) | | -8(y+1)=40 | | A=35+28x21-14 | | 4+1-4w=6 | | -14+29=-5(x+1) | | 50=-16x^2+112x | | 7x+2=4×+23 | | 0.57x=12 | | 5/3x-4=7/3x-5 | | (3x+15)+(14x-9)=90 | | 7x+5=3x+13+2x | | -9(t+2)=4(t=15) | | 34-3x=4 | | 5x+7=-3x+23 | | -14-14h=-15h+18-h | | (2+2x)+62=180 | | 3x-8x+5=30 | | -30/6=x | | 7x+9-3x=41 | | 4x-10+7x-8=90 | | 2s-6=s+14 | | 10(h+1)=-4=76 | | 6x+16=-19 | | 5.3=-7+x | | 6b-11=49 | | 39x=12(x+4) | | -8+m/4=3 | | -3(p-4)=3(p+7) |

Equations solver categories